Successful Primary Therapy With Posaconazole for Fulminant Progressive Disseminated Histoplasmosis in a Renal Transplant Recipient. Issue 1 (January 2018) - Akram, Sami; Sundareshan, Vidya; West, Bradford; Prakash, Vidhya; Bergman, Scott; Koirala, Janak
Abstract : Abstract: For severe cases of progressive disseminated histoplasmosis (PDH), Infectious Diseases Society of America recommends treatment with liposomal amphotericin B for 2 weeks followed by itraconazole. In patients who are at risk for renal failure and for renal transplant patients on multiple nephrotoxic medications, there are no alternatives currently in clinical use. Posaconazole has shown promise in the animal experiments and also as salvage therapy in patients who have failed therapy with polyene and azole antifungal agents. Posaconazole has seldom been used as an initial drug for severe cases of PDH. We report a case of a renal transplant patient with severe PDH, on immunosuppressive therapy, successfully treated with posaconazole. Abstract : There are not many options for treating severe forms of histoplasmosis according to the guidelines. Amphotericin has nephrotoxicity while itraconazole is slow to reach therapeutic levels and not suitable for severe forms of histoplasmosis. Posaconazole has proven to be as effective as amphotericin B in animal experiments. Clinically, posaconazole has been used successfully as salvage therapy but posaconazole as the primary therapy has rarely been reported. The authors found no such report in PubMed.